Evaluasi Kerapatan Tanam dan Metode Pengendalian Gulma pada Budidaya Padi Tanam Benih Langsung di Lahan Sawah Pasang Surut - Imelda S. Marpaung; Yakup Parto; Erizal Sodikin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Weed is one of limiting factors in the direct-seeded rice cultivation. Cost incurred by farmers to control weeds is still quite high. Various techniques of weed control need to be evaluated to obtain the most effective weed control in tidal land. The experiment was conducted in tidal land fields in the Telang Sari village Tanjung Lago Sub District Banyuasin District during November 2012−March 2013. The experiment was arranged in a split plot design with planting density (K) as main plot and weeding methods (P) as sub plot. Five levels of planting density at 20, 40, 60, 80 and 100 kg rice seed/ha and four levels of weeding methods (manual weeding, dimethyl amine herbicide, penoxulam, and no weeding) were used in the experiment. The treatment was repeated 3 times and applied in 4×3m plot. Components of plant growth and yield of rice plants were measured and analyzed using Microsoft Excel and SPSS 17.0. The results showed that methods of weed control did not significantly affect plant height, plant biomass at 4 weeks after seeding and number of tillers, but significantly affect number of empty grain and filled grain per panicle. Both planting density and method of weed control significantly affect yield, but no significant interaction between treatments. Planting density did not significantly affect plant biomass from age 8 weeks after seeding. Yield of planting density at 80 kg seed/ha was not significantly different from the yield of 40−60 seed/ha. Method of weed control was significantly affecting the rice yield. Weed control can increase crop yields by 37.7%.